2000
DOI: 10.1104/pp.122.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance and Induction by Solar Radiation of Ultraviolet-Absorbing Sunscreens in Field-Grown Soybean Crops

Abstract: Colorless phenylpropanoid derivatives are known to protect plants from ultraviolet (UV) radiation, but their photoregulation and physiological roles under field conditions have not been investigated in detail. Here we describe a fast method to estimate the degree of UV penetration into photosynthetic tissue, which is based on chlorophyll fluorescence imaging. In Arabidopsis this technique clearly separated the UV-hypersensitive transparent testa (tt) tt5 and tt6 mutants from the wild type (WT) and tt3, tt4, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
235
0
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(255 citation statements)
references
References 30 publications
11
235
0
7
Order By: Relevance
“…A folha adulta manteve ainda redução de 23% do ETR em relação ao momento inicial, em que as plantas estavam ainda sem herbicida em solução. Destaca-se também que algumas pequenas oscilações do ETR no período avaliado devem-se às condições do ambiente (Mazza et al, 2000). Para D. horizontalis, com quatro horas após a disponibilidade do herbicida em solução, ocorreu redução de 17% do ETR para a folha adulta, em relação ao valor de ETR inicial da folha sem herbicida.…”
Section: Resultsunclassified
“…A folha adulta manteve ainda redução de 23% do ETR em relação ao momento inicial, em que as plantas estavam ainda sem herbicida em solução. Destaca-se também que algumas pequenas oscilações do ETR no período avaliado devem-se às condições do ambiente (Mazza et al, 2000). Para D. horizontalis, com quatro horas após a disponibilidade do herbicida em solução, ocorreu redução de 17% do ETR para a folha adulta, em relação ao valor de ETR inicial da folha sem herbicida.…”
Section: Resultsunclassified
“…The former strategy is facilitated by UV-induced morphology changes including the increase of epidermal UV absorption [4], and moving the site of photosynthesis away from upper regions of adaxial palisade cells towards the inside of the leaf [37]. An application of UVinducible chlorophyll fluorescence demonstrated the penetration of 305 nm UV-B into Arabidopsis and soybean leaves, and that UV-B reached chlorophyll containing tissues even in sunlight acclimated leaves having strong epidermal UV screening [38]. These results show the need for the second, antioxidant line of defense.…”
Section: Uv and Antioxidantsmentioning
confidence: 99%
“…The defence mechanism by increased UV-B absorbing compounds partly counteracts the harmful effects of UV-B radiation. Both field and in vitro studies have shown that certain flavonoids and non-specified phenolics can protect DNA from UV-B induced damage (KOOSTRA, 1994;MAZZA et al, 2000).…”
Section: Introductionmentioning
confidence: 99%